Pengembangan Modul Kimia Muatan Lokal Valid dan Praktis Tentang Pakan Ampas Tahu Terfermentasi untuk Pertumbuhan Ikan Patin Berbasis STEM-PBL - Sari Marlisyah; K Anom; Made Sukaryawan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
This research is a development research that aims to produce a local integrated chemical module that integrates STEM Problem Based Learning which is valid and practical. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation) and evaluated by Tessmer formative method. Tessmer formative evaluation stages in this study include evaluation, expert review, one-to-one and small group. The results of the expert review stage obtained the average score of the validity of 0.76 Aiken scale with the category is very valid. For the final score the practicality is obtained from one-to-one test of 0.67 Aiken scale (practical) and small group 0.75 Aiken scale (practical). Based on the evaluation results show that the resulting module has met the valid and practical criteria. It is suggested that this module can be used as an alternative material for entrepreneurship subject.